Computational fluid dynamic measures of wall shear stress are related to coronary lesion characteristics. Issue 20 (14th June 2016) - Park, Jun-Bean; Choi, Gilwoo; Chun, Eun Ju; Kim, Hyun Jin; Park, Jonghanne; Jung, Ji-Hyun; Lee, Min-Ho; Otake, Hiromasa; Doh, Joon-Hyung; Nam, Chang-Wook; Shin, Eun-Seok; De Bruyne, Bernard; et al.
Abstract : Objective: To assess the distribution of pressure and shear-related forces acting on atherosclerotic plaques and their association with lesion characteristics using coronary CT angiography (cCTA)-based computational fluid dynamics (CFD) model of epicardial coronary arteries. Methods: Patient-specific models of epicardial coronary arteries were reconstructed from cCTA in 80 patients (12 women, 63.8±9.0 years). The pressure and wall shear stress (WSS) in left anterior descending coronary arteries were assessed using CFD. High-risk plaques were defined as the presence of at least one of the following adverse plaque characteristics: low-density plaque, positive remodelling, napkin-ring sign and spotty calcification. Results: At resting condition, 39.5% of stenotic segments (% diameter stenosis 52.3±14.4%) were exposed to high WSS (>40 dyne/cm 2 ). When the stenotic lesion was subdivided into three segments, the distribution of WSS was different from that of pressure change and its magnitude was highest at minimal lumen area (p<0.001). High pressure gradient, proximal location, small lumen and short length were independent determinants of WSS (all p<0.05). The plaques exposed to the highest WSS tertile had a significantly greater proportion of high-risk plaques. The addition of WSS to % diameter stenosis significantly improved the measures of discrimination and reclassification of high-risk plaques (area under the curves from 0.540 to 0.718, p=0.031; net reclassification index 0.827, p<0.001). Conclusions: The cCTA-based CFD method can improve the identification of high-risk plaques and the risk stratification for coronary artery disease patients by providing non-invasive measurements of WSS affecting coronary plaques.